Is a pulmonary rehabilitation program effective in COPD patients with chronic hypercapnic failure?. (3rd May 2016) - Sahin, Hulya; Naz, Ilknur; Varol, Yelda; Aksel, Nimet; Tuksavul, Fevziye; Ozsoz, Ayse
ABSTRACT: Objectives : Our study aimed to compare the effectiveness of a pulmonary rehabilitation (PR) program between hypercapnic and normocapnic patients with chronic obstructive pulmonary disease (COPD). Methods : Hypercapnic (Group 1) and normocapnic (Group 2) patients with COPD who participated in this study underwent a comprehensive 8-week out-patient PR program. Results : A total of 122 patients were enrolled in the study; (n:86, n:36 groups 1 and 2, respectively.) After PR, both groups had better symptom scores as well as physical, social and emotional functioning. In addition, the groups had reduced dyspnea, anxiety and depression scores. After PR, the hypercapnic group improved significantly more in exercise capacity (∆6 MWT 50 m. vs 40 m.) compared with normocapnic patients (p=0.044). The hypercapnic group demonstrated a significant reduction in the PaCO2 levels after PR within (p<0.05) and between groups (p<0.0001). Conclusions : Given the significant reductions in pCO2 levels and significant increases in exercise capacity and QoL parameters after PR, the patients with chronic hypercapnic failure apparently benefited from the PR.